2023
DOI: 10.3390/jcm12134534
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm vs. Rate Control in Patients with Postoperative Atrial Fibrillation after Cardiac Surgery: A Systematic Review and Meta-Analysis

Abstract: Background: Postoperative atrial fibrillation (POAF) is the most common complication after cardiac surgery; it is associated with morbidity and mortality. We undertook this review to compare the effects of rhythm vs. rate control in this population. Methods: We searched MEDLINE, Embase and CENTRAL to March 2023. We included randomized trials and observational studies comparing rhythm to rate control in cardiac surgery patients with POAF. We used a random-effects model to meta-analyze data and rated the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The findings of the CTSNet trial are further confirmed by a systematic review by Ahmed et al of eight RCTs and 990 patients that compared rate versus rhythm control. The review found no clear advantage to a rate- or a rhythm-control strategy ( 73 ). A survey of American (n=262) and European (n=379) anesthesiologists found certain differences in their use of different drugs for POAF prophylaxis, specifically beta-blockers (American 60% vs. European 53%), amiodarone (39% vs. 34%), and supplemental magnesium (37% vs. 65%) ( 74 ).…”
Section: Management Of Postoperative Afmentioning
confidence: 99%
“…The findings of the CTSNet trial are further confirmed by a systematic review by Ahmed et al of eight RCTs and 990 patients that compared rate versus rhythm control. The review found no clear advantage to a rate- or a rhythm-control strategy ( 73 ). A survey of American (n=262) and European (n=379) anesthesiologists found certain differences in their use of different drugs for POAF prophylaxis, specifically beta-blockers (American 60% vs. European 53%), amiodarone (39% vs. 34%), and supplemental magnesium (37% vs. 65%) ( 74 ).…”
Section: Management Of Postoperative Afmentioning
confidence: 99%
“…In the Special Issue "New Frontiers in Electrocardiography, Cardiac Arrhythmias, and Arrhythmogenic Disorders" of the Journal of Clinical Medicine, readers will find 22 papers (summarized in Table 1) written by authors from around the world (Figure 1). These papers concern a variety of topics in the field of electrocardiology [20][21][22]. In the rapidly growing field of electrocardiology, further in-depth analyses of pathogenesis and clinical management, along with important aspects of telehealth, which is promising for the improvement of care [23], are needed.…”
mentioning
confidence: 99%